Efficacy of fipronil (1.0 mg/kg) against Rhipicephalus (Boophilus) microplus strains resistant to ivermectin (0.63 mg/kg) - Zanetti Lopes, Welber Daniel [UNESP]; Cruz, Breno Cayeiro [UNESP]; Pires Teixeira, Weslen Fabricio [UNESP]; Felippelli, Gustavo [UNESP]; Maciel, Willian Giquelin [UNESP]; Buzzulini, Carolina [UNESP]; Costa Gomes, Lucas V. [UNESP]; Favero, Flavia [UNESP]; Soares, Vando Edesio [UNESP]; Bichuette, Murilo A. [UNESP]; Oliveira, Gilson Pereira de [UNESP]; Costa, Alvirnar Jose da [UNESP] (Elsevier B.V., 2014)
The present study aimed to evaluate the efficacy of fipronil (1 mg/kg) against three strains of ivermectin-resistant Rhipicephalus (Boophilus) microplus (R. (B.) microplus), naturally infesting cattle from different states of Brazil. Three rural properties with a history of macrocyclic lactones ineffectiveness against the cattle tick, and low frequency use of fipronil in the herd, were selected for the study. The animals were randomized according to the mean tick counts, performed on days 3, 2 and I, into three groups with 10 animals each: T01, control (saline solution); T02, subcutaneous ivermectin (0.63 mg/kg) and T03, topical fipronil (1 mg/kg). Treatment was performed on day 0. Counts of partially engorged female ticks were performed on days 3,7 and 14 post-treatment (DPT), and then every 7 days until the 49th DPT. In all three experiments, it was possible to diagnose resistance of R. (B.) microplus to ivermectin (0.63 mg/kg). The maximum efficacy (arithmetic mean) obtained for ivermectin was 64% in experiment II. On the other hand, the formulation containing fipronil (1 mg/kg) reached high efficacy values (>= 97%) in all three experiments. The results from all experiments in this study demonstrate the high efficacy of 1 mg/kg fipronil, administered pour-on in naturally infested cattle, against strains of R. (B.) microplus that are resistant to 630 mcg/kg ivermectin. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Efficacy; Fipronil; Ivermectin; Resistance